1983
DOI: 10.1080/00049158.1983.10674378
|View full text |Cite
|
Sign up to set email alerts
|

Snow damage in Australian pine plantations

Abstract: In June 1981 heavy falls of wet snow with air temperatures near 0°C and strong winds caused extraordinary damage in both pine plantations and native eucalypt forests in much of southeastern Australia, especially at altitudes between 700 m and 1200 m. Using data from a thinning trial, inventory plots, forestry records and extensive inspections of plantations and arboreta, a study was made of this damage to identify types, incidence and mechanisms of damage in Pinus radiata plantations, and their silvicultural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The patterns of damage to the stems of such eucalypts were similar to those recorded in the pine plantations (Cremer et al 1983). The incidence of bent and broken stems was simiDownloaded by [New York University] larly influenced by the slenderness of the stems, the lean of the trees, the imbalance of the crowns, and the proximity between trees (the chance of one tree collapsing on and bringing down its neighbours).…”
Section: Damage To Young Forests Of Even Agementioning
confidence: 58%
See 1 more Smart Citation
“…The patterns of damage to the stems of such eucalypts were similar to those recorded in the pine plantations (Cremer et al 1983). The incidence of bent and broken stems was simiDownloaded by [New York University] larly influenced by the slenderness of the stems, the lean of the trees, the imbalance of the crowns, and the proximity between trees (the chance of one tree collapsing on and bringing down its neighbours).…”
Section: Damage To Young Forests Of Even Agementioning
confidence: 58%
“…The damage to the eucalypts was examined by walking some 50 to 100 km in the mountain forests in the ACT, NSW and Victoria, and by driving for hundreds of kilometers through the forests. The paper complements a more detailed study made of snow damage in pine plantations (Cremer et al 1983), in which the incidence of snow damage is examined in relation to tree characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Given the significant negative correlation detected between breeding values of height-diameter ratios and height and diameter for Scots pine and Norway spruce, the breeding programs for these species need to select for other traits in order to avoid reductions in the height-diameter ratio in improved material. However, maintaining the same height-diameter ratio as unimproved material may not necessarily be optimal, as there may be sound silvicultural and commercial reasons for adjusting it (Cremer et al 1983;Lohmander and Helles 1987;Harrington and DeBell 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In Swedish conditions, genetic differences in stem slenderness might justify adjustments of (for example) the diameter-height models presented by Fahlvik and Nyström (2006). Furthermore, stem slenderness is often used to determine tree stability and susceptibility to windthrow and snow damage (Cremer et al 1983;Lohmander and Helles 1987;Harrington and DeBell 1996). In a study on five tree species in Canada, Wang et al (1998) found that stem slenderness was negatively correlated with tree diameter at breast height (dbh), height, crown length and age, but positively correlated with stand density, species composition, and site index.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows a trunk-bending scenario in Toyama, Japan. The degree of snow damage depends on several factors, including forest stand and geographic characteristics (Cremer et al, 1983;Kato and Nakatani, 2000;Jalkanen and Mattila, 2000). In our analysis candidate variables include geographic elements such as slope aspect, and forest stand attributes such as stand age and average tree height.…”
Section: Data For Snow Damagementioning
confidence: 99%